2023
DOI: 10.1097/sle.0000000000001178
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Single-site Robotic Cholecystectomy: A Cumulative Sum Analysis

Abstract: Background: Minimally invasive surgery has significantly improved cosmesis and clinical outcomes after either laparoscopic or robotic cholecystectomy. In an effort to minimize the number of incisions in multiport procedures, single-site approaches have been developed. However, single-site robotic cholecystectomy (SSRC) can be technically challenging for novice surgeons. The goal of this study is to establish the learning curve (LC) of SSRC through an assessment of operative times and clinical outcomes. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They also mentioned that a controversial opinion raised by Pietrabissa et al 43 , that no difference in postoperative pain was observed between SIRC and CMLC, was probably due to a large loss to follow-up. In terms of the learning curve (LC), Kudsi et al 75 reported in a retrospective cumulative sum analysis establishing the LC of SIRC through an assessment of operative times and clinical outcomes that a steady decrease in skin-to-skin time was observed during the completion of the first 91 consecutive cases, in which a single MIS-trained surgeon performed more than 250 consecutive SIRC procedures. However, in previous retrospective studies, the LC of SIRC was established at a smaller number of 40–48 cases, with the mean operative time ranging from 45 to 83 min 36 , 42 , 54 .…”
Section: The Research Status Of Sirasmentioning
confidence: 99%
“…They also mentioned that a controversial opinion raised by Pietrabissa et al 43 , that no difference in postoperative pain was observed between SIRC and CMLC, was probably due to a large loss to follow-up. In terms of the learning curve (LC), Kudsi et al 75 reported in a retrospective cumulative sum analysis establishing the LC of SIRC through an assessment of operative times and clinical outcomes that a steady decrease in skin-to-skin time was observed during the completion of the first 91 consecutive cases, in which a single MIS-trained surgeon performed more than 250 consecutive SIRC procedures. However, in previous retrospective studies, the LC of SIRC was established at a smaller number of 40–48 cases, with the mean operative time ranging from 45 to 83 min 36 , 42 , 54 .…”
Section: The Research Status Of Sirasmentioning
confidence: 99%